Knowledge and Attitude Regarding Arteriovenous Fistula Care among Patient under Maintenance Hemodialysis at Bharatpur Hospital - Bhusal , Mina Kumari; Nepali, Sunita; Aryal, Neelu; Regmi, Kamala; Sapkota, Devi Kumari (Journal of Bharatpur Hospital, 2025)
Background End-Stage Renal Disease (ESRD), is a severe medical condition where the kidneys have permanently lost their ability to function, which requiring dialysis or a kidney transplant to survive, often requiring an arteriovenous fistula (AVF) for hemodialysis. Proper care of the AVF is crucial to prevent complications. This study aimed to assess knowledge and attitude of the patient towards the AVF care in Bharatpur hospital. Methods A descriptive cross-sectional study carried out among 150 Patients under Maintenance Hemodialysis at Bharatpur Hospital, Chitwan by applying purposive sampling method from June 16 to July 2, 2024 using semi-structured interview schedule to assess knowledge and Five Point Likert Scale to assess attitude. Informed written consent was obtained to ensure their rights. The data were analyzed in SPSS 16 version by using descriptive Statistical tool. Results Among 150 patients almost all (97.3%) of respondents good knowledge and minority 0.7% had poor knowledge regarding AVF care. About 52.7% respondents’ shows negative attitude towards the AVF care where as 47.3% respondent shows the positive attitude. Conclusions Almost all of the respondents have good knowledge and majority of the respondents had positive attitude towards living a normal life as long as they adhere to the treatment and AVF care, and majority of the respondent’s showed confidence in ability to manage AVF care by themselves.